INFLUENCE MODEL LEARNING INQUIRY TRAINING LOCAL WISDOM BASED ON BATAK TOBA HIGH ORDER THINKING SKILL (HOTS) ABILITY PHYSICS IN SMA - Eliyana .; Chintya Maretti Pandiangan; Halimatun Sakdiah; Rita Juliani (Universitas Negeri Medan, 2019)
Research has been carried out on the influence of inquiry learning training models based on the local wisdom of Toba Batak on the ability of high order thinking skills (HOTS) physics which aims to improve HOTS's abilities in physics learning. The study was conducted at two schools in the city of Medan, namely MAN 1 and SMAN 21. The type of research was quasi-experimental with two group pretest-posttest design, conducted on 67 experimental class students treated with inquiry learning training models based on Toba Batak wisdom and 67 control class students treated with conventional learning in class XI. The instrument used was the HOTS ability test in the form of an essay with 10 validated questions. The instrument is given before and after being treated. The results of the HOTS ability test were analyzed using the t-test and n-gain to calculate the improvement criteria. The results of hypothesis testing using the t test with α = 0.05 there are significant differences due to the influence of the inquiry learning training model based on the local wisdom of Toba Batak in improving HOTS in XI class physics learning.